Influence of a 2‐ to 6‐year physical education intervention on scholastic performance: The CHAMPS study‐DK. (22nd May 2017) - Bugge, Anna; Möller, Sören; Tarp, Jakob; Hillman, Charles H.; Lima, Rodrigo Antunes; Gejl, Anne Kær; Klakk, Heidi; Wedderkopp, Niels
Abstract : The aim of this study was to investigate the influence of a school‐based intervention with a tripling of physical education (PE) lessons from two (90 minutes) to six lessons per week (270 minutes) on scholastic performance. This study is part of the CHAMPS study‐DK, a quasi‐experimental study that began in 2008. The intervention group consisted of six schools, and the control group consisted of four matched schools (mean age at baseline=8.4 years, kindergarten class fourth grade). Academic performance was extracted from the national test system from 2010 to 2014 (Math and Danish were measured at third and sixth, and second, fourth and sixth grades, respectively). Participants included 1888 students participating in at least one scholastic performance test. Linear mixed models were applied to test for differences between groups and adjusted for known confounders. No significant differences were observed between groups in the academic performance tests (control group reference); Danish second grade β=−1.34 (95% CI −9.90, 7.22), fourth grade β=0.22 (95% CI −6.12, 6.56), sixth grade β=1.03 (95% CI −5.02, 7.08), and all grades combined β=0.28 (95% CI −5.74, 6.31) and Math third grade β=−2.87 (95% CI −9.65, 3.90), sixth grade β=0.99 (95% CI −7.36, 9.34) and combined β=−1.20 (95% CI −8.10, 5.71). In conclusion, no significant differences were observed between intervention and control schools for scholastic performance. Importantly, there were no negative effects of additional PE on scholastic outcomes, despite more PE and longer school days for intervention children.